O049 Insomnia severity and cognitive performance following two weeks' nightly supplementation with 150mg Cannabidiol (CBD) for primary insomnia. (9th November 2022) - Narayan, A; Downey, L; Hayley, A
Abstract: Introduction: Cannabidiol (CBD) may have sleep promoting effects, but clinical dosage and safety recommendations are still lacking. This study was the first to examine whether the approved Therapeutic Goods Association (TGA) daily over-the-counter maximum dose of oral CBD oil (150mg) improved the self-rated severity of primary insomnia and explored CBD effects on higher-order cognitive performance tasks. Methods: Participants (n = 30) with moderate-severe primary insomnia completed a one-week single-blind placebo-run in period followed by a 2-week double blind, parallel, randomised placebo-controlled dosing period with four assessment visits (V0-V4). Intra-group and between-group Insomnia Severity Index (ISI) (V0 and V4) and cognitive performance (ECog Pro) (V1, V2 and V4) outcomes were assessed using paired sample t-test with independent t-tests, and separate linear mixed effect models with Maximum Likelihood Estimation and independent T-tests, respectively. Results: Preliminary findings showed reduced ISI for treatment (n = 5; baseline mean 16.60 to 9.60 post treatment, mean difference = -7.00, SD = 4.47) and placebo (n = 8; baseline mean 18.13 to 9.25 post treatment, mean difference = -8.88, SD = 3.68) over time (both p < .001). At conclusion, CBD did not outperform a placebo (p = .427). Numeric and spatial working memory accuracy (%) and reaction time (ms) indicated no intra-group or between-group differences at any time point (all p > 0.05). Discussion: Decreased insomnia severity from moderate to subthreshold levels indicate potential clinical benefits of daily CBD supplementation as a sleep aid for primary insomnia. Preserved higher-order neurocognitive abilities suggest a good safety profile.